Summary of readings in neurosurgery brain - Jafri Malin Abdullah (Academic imprint series, 2013)
If you are looking for a straightforward and readable summary of neurosurgical cases, this book is the best for you. This book can provide you with convenient means of reference especially for medical practitioners, and can be a good guide for everyone that has interest in the neurosurgery field. Summary of Readings in Neurosurgery: Brain is the book for readers who need to know about neurosurgery for brain. It is presented in clear, subject by subject briefings with examples and pictures to illustrate the application of the neurosurgery and to help readers understand various topics and cases related to neurosurgery and brain which have been discussed based on the researches and current practices up to 2011. This book is written by experienced authors in the Malaysian neuroscience field in a short form, to ease and give a relaxing reading experience to all readers. Therefore, we hope that all readers will very much enjoy this work as well as find it immensely educative